1982
DOI: 10.1007/bf02535373
|View full text |Cite
|
Sign up to set email alerts
|

Estolide triglycerides ofTrewia nudiflora seed oil

Abstract: The seed oil of Trewia nudiflora is known to contain glycerides of c~-kamlolenic (18-hydroxy-cis-9,trans-ll,trans-13-octadecatrienoic) acid. We have shown that a large part of these glycerides contain estotides in which the hydroxyl group of a-kamlolenic acid is esterified to a molecule of another acid, either a hydroxy acid or an ordinary fatty acid. By preparative thin layer chromatography, we isolated a series of tri-, tetra-, penta-and hexaacyl glycerols. By lipolysis and gas chromatography-mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…The fatty acid compositions are given in Table 1. Results confirmed that both species contained kamlolenic acid (K) as the predominant fatty acid at levels similar to those reported previously [2,4]. As no mass spectra for this fatty acid are available we have presented the mass spectrum of the trimethyl-silyl derivative of kamlolenic FAME (K-TMS FAME) in Fig.…”
Section: Identification Of Fatty Acidssupporting
confidence: 88%
See 2 more Smart Citations
“…The fatty acid compositions are given in Table 1. Results confirmed that both species contained kamlolenic acid (K) as the predominant fatty acid at levels similar to those reported previously [2,4]. As no mass spectra for this fatty acid are available we have presented the mass spectrum of the trimethyl-silyl derivative of kamlolenic FAME (K-TMS FAME) in Fig.…”
Section: Identification Of Fatty Acidssupporting
confidence: 88%
“…Characterization of M. philippensis oil by lipase hydrolysis and thin layer chromatography suggested that TAG-estolides were symmetrical in structure with FA-estolides of up to three fatty acids in the sn-1 and sn-3 positions and either kamlolenic acid or a di-kamlolenic acid FA-estolide at the sn-2 position [3]. Examination of oil from T. nudiflora suggested that the FA-estolide components of this species contained predominantly two fatty acids, only one of which was kamlolenic acid [4].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, toxic cyanolipids and wax esters were reported only for Sapindaceae [48] and Jojoba seed oils [47], respectively. Acetoglycerides were found in the seed oils of species from the Celastraceae, Lardizabalaceae, Ranunculaceae, Rosaceae [49,50], and Balsaminaceae [51], and tetra-and pentaacylglycerides appeared in Euphorbiaceae, Cruciferae, Polygalaceae and Compositae [45].…”
Section: Fatty Acids and Lipids Vs Chemotaxonomymentioning
confidence: 99%
“…The kernel oil of Chinese tallow (Sapium sebiferum) seed contains tetraester triglycerides composed of trans-2,cis-4-decadienoic acid joined in an estolide linkage to 8-hydroxy-5,6-octadienoic acid [137]. Trewia nudifl ora (false white teak) seed oil contains glycerides of α-kamlolenic (18-hydroxy-9,11,13-octadecatrienoic) acid, largely as estolide triglycerides [138].…”
Section: Estolide Ester Base Stocksmentioning
confidence: 99%